Surveying knowledge, practice and attitudes towards intervention fidelity within trials of complex healthcare interventions - McGee, Daragh; Lorencatto, Fabiana; Matvienko-Sikar, Karen; Toomey, Elaine (Current controlled trials in cardiovascular medicine, 2018)
Background Intervention fidelity is the degree to which interventions have been implemented as intended by their developers. Assessing fidelity is crucial for accurate interpretation of intervention effectiveness, but fidelity is often poorly addressed within trials of complex healthcare interventions. The reasons for this are unclear, and information on the use of methods to enhance and assess fidelity in trials of complex interventions remains insufficient. This study aimed to explore the knowledge, practice and attitudes towards intervention fidelity amongst researchers, triallists and healthcare professionals involved with the design and conduct of trials of complex healthcare interventions. Methods An online survey consisting of closed and open-ended questions exploring four sections (Demographics, Fidelity knowledge, Practice and Attitudes) was conducted. This was an opportunistic sample of individuals with experience of direct involvement in trials of complex healthcare interventions (e.g. design/development, conduct, evaluation). Results Data from 264 participants representing 15 countries were analysed. The majority (65.9%, n = 174) of participants identified themselves as ‘Researchers’. The majority of participants were familiar with the term “intervention fidelity” (69.7%, n = 184) and indicated that fidelity is important (89.7%, n = 236). Mean self-reported understanding of fidelity was moderate. Although 68% ( n = 182) had previously used strategies to assess (e.g. audio/video-recording sessions) and enhance (e.g. training manual) fidelity in trials of complex interventions, only a limited proportion of participants indicated always reporting these strategies in subsequent publications (30.9%, n = 56). Poor knowledge or understanding was the most commonly cited barrier to addressing intervention fidelity in trials (77.4%, n = 202). Over half of respondents (52.1%, n = 137) had never completed specific fidelity training or research, and the vast majority (89.7%, n = 236) would welcome specific training in this area. Conclusion Despite good awareness of intervention fidelity and its importance, poor knowledge and understanding appears to be a key factor limiting how intervention fidelity is addressed in trials of complex interventions. Participants identified a need for further training and education in this area. Additionally, clarification of the terminology, definition and components of intervention fidelity would facilitate better understanding of the concept. A discrepancy between participants’ use of fidelity strategies and subsequent reporting raises concerns around inadequate fidelity reporting in the trials literature.